Remember that, in general, a quadratic equation can be written as:
![ax^2+bx+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/knmog89o03f8dx9fluvbqb64q9rt61y6kp.png)
In our problem, we already have the values of a and b, c is the missing value. When this happens, that a and b are given, the value of c is equal to:
![c=((b)/(2))^2](https://img.qammunity.org/2023/formulas/mathematics/college/q319c5ppcp6ith6v92kv44b7at03vf148l.png)
Therefore, the missing value in the problem is:
![\begin{gathered} b=-2 \\ \Rightarrow c=(-(2)/(2))^2=(-1)^2=1 \\ \Rightarrow c=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pxz0ukh9lau3pynwtbw75xsrjfmeld047s.png)
Thus, the answer is 1
We can easily verify that this answer is correct as follows:
![x^2-2x+1=(x-1)(x-1)=(x-1)^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/8l6gxm5uj8cygh5wmhip9g7j3iun1473ua.png)